1994
DOI: 10.3354/meps115219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of suspended mussel culture (Mytilus spp.) on sedimentation, benthic respiration and sediment nutrient dynamics in a coastal bay

Abstract: Many studies have shown that the pnmary effect of shellfish culture on nearshore m a n n e systems is enhanced sedimentation T h~s study was d e s~g n e d to measure the effects of this enhanced sedimentation on the respiration and nutrlent fluxes of the benthic community and the coupling between the pelagic and b e n t h~c systems at a mussel culture s~t e (Mytllus edulls and M trossulus) In Upper South Cove, Nova Scotia, Canada There was a signif~cant association between chlorophyll In the water colun~n and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
104
5
4

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(123 citation statements)
references
References 18 publications
10
104
5
4
Order By: Relevance
“…Additional research has indicated that TOC appears to be toxic to benthic fauna at concentrations over 35 mg g -1 due to the deoxygenating effect of organic matter, whereas benthic assemblages do not show any evident alterations at TOC concentrations below 10 mg g -1 (Hyland et al, 2005). Most forms of bivalve shellfish culture contribute to Figures in parentheses are the % significance levels in a permutation test for the absence of seriation Hydrobiologia enhanced sedimentation of organic material in the proximity of the mariculture units (Dahlbäck & Gunnarsson, 1981;Hatcher et al, 1994;Grant et al, 1995), and in one study, suspended scallop culture increased the deposition of organic matter to approximately 2.46 times compared to the rate of a reference site without scallop culture (Zhou et al, 2006). However, in our study, the organic matter did not differ along the distance gradient, with an average of 17.27 ± 6.05 mg g -1 (TOC percentage of weight) lower than the threshold of danger to benthic assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research has indicated that TOC appears to be toxic to benthic fauna at concentrations over 35 mg g -1 due to the deoxygenating effect of organic matter, whereas benthic assemblages do not show any evident alterations at TOC concentrations below 10 mg g -1 (Hyland et al, 2005). Most forms of bivalve shellfish culture contribute to Figures in parentheses are the % significance levels in a permutation test for the absence of seriation Hydrobiologia enhanced sedimentation of organic material in the proximity of the mariculture units (Dahlbäck & Gunnarsson, 1981;Hatcher et al, 1994;Grant et al, 1995), and in one study, suspended scallop culture increased the deposition of organic matter to approximately 2.46 times compared to the rate of a reference site without scallop culture (Zhou et al, 2006). However, in our study, the organic matter did not differ along the distance gradient, with an average of 17.27 ± 6.05 mg g -1 (TOC percentage of weight) lower than the threshold of danger to benthic assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…In several countries, nutrient-laden discharges from aquaculture, agriculture, forestry or sewage have resulted in serious eutrophication-induced oxygen depletion of the water and a high ammonia release from the sediment (Schaubs & Gieskes 1991), both of which have adverse affects on shallow water benthic fauna1 species (Kristensen 1984, Brockmann et al 1988, Parker 1988, Costello et al 1993, Hatcher et al 1994). …”
Section: Introductionmentioning
confidence: 99%
“…Coen et al, 2007;Hatcher et al, 1994;Newell et al, 2005) by consuming seston from the water column and depositing feces and pseudofeces on the sediment surface, thus causing an organic enrichment of the surrounding sediments Krone et al, 2013) especially by increasing the total dissolved nitrogen (Hatcher et al, 1994). These changes in sediment chemistry can affect benthic communities by increasing or decreasing individual species abundances (Dauer et al, 2000) or by changing entire species compositions (Kaspar et al, 1985).…”
Section: Tablementioning
confidence: 99%